Melhoramento genético de palmeiras: validação metodológica de técnicas de descontaminação em culturas de embriões zigóticos e sua influência na atividade morfogenética sob efeito de indutores auxínicos - Batista, Bianca Gomes (2023)
Aseptic conditions are necessary to prevent contaminations that occur in vitro, whether in instruments, containers, or pure culture media. For this purpose, chemical and physical disinfectant agents are used to eliminate microorganisms. Polyethylene Petri dishes are disposable, generating solid waste and, consequently, trash. Therefore, it is necessary to create effective protocols for decontaminating this material, aiming at reuse and waste reduction. Culture media are typically sterilized using autoclaving. However, certain growth regulators (GR) from the auxin group degrade in the presence of high temperatures, raising doubts about the chemical stability of other GR belonging to this group. The objective of this work was to create sterilization methods for polyethylene Petri dishes and culture media with different auxin inducers, using zygotic embryos from the palm trees Euterpe edulis, Euterpe edulis Santa Marta ecotype, and Euterpe oleracea as test plants. Experimento 1 was conducted in a 4x4 factorial design (Sodium hypochlorite (NaOCl): 0, 6, 12, 24 hours x Ultraviolet light (UV): 0.5, 1.0, 1.5, 2.0 hours), with four replicates of 10 Petri dishes each. Experiment 2 was carried out with three UV light treatments (4, 6, 10 hours), with four replicates of eight Petri dishes each. Experiment 3 was conducted in a 2x5 factorial design (Sodium dichloroisocyanurate (NaDCC): 0, 24 hours x UV: 6, 12, 18, 24, 36 hours), with four replicates of eight Petri dishes each. Experiment 4 was conducted in a 2x3 factorial design (MS: non-autoclaved, autoclaved x UV light distance: 10, 30, 50 cm), with four replicates of five Petri dishes each. Experiment 5 was carried out with five UV light treatments (1, 2, 3, 4, 5 hours), with four replicates of eight Petri dishes each. Experiment 6 was conducted in a 3x4 factorial design (Palms: Euterpe edulis; Euterpe edulis Santa Marta ecotype; Euterpe oleracea x filtered picloram; filtered triclopyr; autoclaved picloram; autoclaved triclopyr). The combination of NaDCC (24 hours) and UV (3 hours) exposure is ideal for achieving effective elimination of microorganisms in disposable Petri dishes. The combination of NaDCC (24 hours) and UV (3 hours) exposure is ideal for achieving effective elimination of microorganisms in disposable Petri dishes. The use of Petri dishes disinfected with NaDCC (1%) for 24 hours, containing both autoclaved and non-autoclaved medium, showed that a distance of 50 cm resulted in absence or low rates of contaminations. The sterilization protocol for culture media and Petri dishes using NaDCC and UV light resulted in the absence or low incidence of contaminations. The species exhibited different behaviors under the influence of the same concentrations of growth regulators; the study revealed that E. edulis and E. edulis Santa Marta ecotype showed a higher responsiveness to somatic embryogenesis induction compared to the species E. oleracea.